1981
DOI: 10.1177/00220345810600120201
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Stimulated Salivary Flow Rate and pH to Lactobacillus and Yeast Concentrations in Saliva

Abstract: This study demonstrates that the presence of yeast, but not lactobacillus infection, is related to salivary flow rate. Salivary pH is correlated with the primary infection of both lactobacilli and yeasts. The low output of saliva appears to influence the quantity of lactobacilli more than that of yeasts. The flow rate was lower and the presence of yeasts was higher in females than in males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
60
1
3

Year Published

1982
1982
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 18 publications
(1 reference statement)
10
60
1
3
Order By: Relevance
“…This result is in agreement with previous studies [37,38]. On contrast, other studies found that lower salivary flow rates play a significant role in caries development [39,40].…”
Section: Discussionsupporting
confidence: 94%
“…This result is in agreement with previous studies [37,38]. On contrast, other studies found that lower salivary flow rates play a significant role in caries development [39,40].…”
Section: Discussionsupporting
confidence: 94%
“…Saliva specimens were taken, at least one hour after a meal, between 9 a.m. and 3 p.m., using the standardized procedures described by PARVINEN & LARMAS (27). Paraffin stimulated saliva was collected by having patients spit into a graduated glass tube for a five-minute period.…”
Section: Methodsmentioning
confidence: 99%
“…The normal value of paraffin stimulated salivary flow rate in healthy adults varies from 1 .O to 3.0 ml/min (9) and is defined as 2.0f0.8 ml/min for men and 1.7kO.7 ml/min for women (27). According to ERICSSON & HARDWICK (9) a flow rate of 0.7 mYmin is very low.…”
Section: Methodsmentioning
confidence: 99%
“…One explanation for this finding may be that the aforementioned risk factors, other than SFR, might also have influenced the calculated caries risk. In addition, stimulated SFR, which contributes as much as 80% to 90% of the average daily salivary production (14), is often selected as a parameter for testing salivary gland function due to its good reproducibility (21,22). Many years ago, Younger et al (23) demonstrated that patients with caries had lower rates of stimulated saliva secretion, compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%